The influence of Sepak Takraw technical skills on athletes at the student education and training center - Padli Padli; Syahril Bais; Jeki Haryanto; Suci Nanda Sari (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2026)
This study examined the changes in technical skills of 15 PPLP sepak takraw athletes over a three-month structured training period, focusing on ball juggling, service, smash, and setting. Using a one-group repeated measures design, athletes’ performances were assessed under standardized conditions in March and June. Results showed significant improvement in ball juggling (mean increase = 43.6 points, F = 61.62, p < .001, η² = 0.81) and smash (mean increase = 5.2 points, F = 9.73, p < .05, η² = 0.66), indicating effective adaptation of coordination and offensive skills. In contrast, service and setting declined significantly, with setting showing the largest decrease (mean = −57 points, F = 29.92, p < .01, η² = 0.91), suggesting insufficient emphasis on precision and tactical drills. Findings highlight the need for balanced training programs integrating coordination, strength, accuracy, and tactical practice. Limitations include small and unequal sample sizes for some skills, and the absence of a control group. Future studies should incorporate control groups and longer-term monitoring to better inform evidence-based training strategies.